Is prostaglandin E2 (PGE2) involved in the thermogenic response to environmental cooling in healthy humans?. Issue 5 (November 2015) - Foster, Josh; Mauger, Alexis R.; Chrismas, Bryna C.R.; Thomasson, Katie; Taylor, Lee
Abstract: Prostaglandin E2 (PGE2 ) is an eicosanoid derived from cyclooxygenase, an enzyme responsible for the cyclisation and oxygenation of arachidonic acid. In response to bacterial infection, PGE2 binds to EP3 receptors on a population of GABAergic neurons in the pre-optic area. Activation of the EP3 receptor decreases the intracellular cyclic adenosine monophosphate (cAMP) concentrations of these neurons, and the resulting dis-inhibition activates spinal motor outputs responsible for shivering thermogenesis, tachycardia, and brown adipose tissue activation. These involuntary responses increase core body temperature to varying degrees depending on the magnitude of infection; an immune response which is crucial for the survival of the host. However, evidence in animal and human models, primarily through the use of cyclooxygenase inhibitors (which block the production of PGE2 ), suggests that PGE2 may also be an important molecule for the defence of core temperature against body cooling and cold stress (in the absence of fever). In this paper, evidence within human and animal models is discussed which supports the hypothesis that the eicosanoid PGE2 has a role in maintaining human core temperature during environmental cooling. Given that over-the-counter PGE2 inhibiting drugs [i.e. Non-Steroidal Anti Inflammatory Drugs (NSAIDS)] are frequently used worldwide, it is possible that the use of such medication during environmental cooling could impair one's ability to thermoregulate. Support for such findings could have major implications in the pathology of hypothermia, thus, we suggest that future researchers investigate this specific hypothesis in vivo, using healthy human models. Suggestions for the implementation of such experiments are provided in the present work.